2017
DOI: 10.1200/jco.2016.70.4767
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Sperm Banking in Adolescents Newly Diagnosed With Cancer: Examination of Adolescent, Parent, and Provider Factors Influencing Fertility Preservation Outcomes

Abstract: Purpose To estimate the prevalence of sperm banking among adolescent males newly diagnosed with cancer and to identify factors associated with banking outcomes. Patients and Methods A prospective, single-group, observational study design was used to test the contribution of sociodemographic, medical, psychological/health belief, communication, and developmental factors to fertility preservation outcomes. At-risk adolescent males (N = 146; age 13.00 to 21.99 years; Tanner stage ≥ 3), their parents, and medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 53 publications
2
77
0
Order By: Relevance
“…Parent or medical team recommendation was associated with increased likelihood of sperm banking completion. 110 Psychosocial providers can assist patients and families in the decision-making process about fertility preservation, particularly when AYA patients are distressed about the potential infertility associated with cancer treatment. 106 The Oncofertility Consortium, a group of clinicians and researchers in the United States, was formed in 2007 to address reproductive barriers facing AYA patients and to identify research priorities in this area.…”
Section: Fertility Preservationmentioning
confidence: 99%
“…Parent or medical team recommendation was associated with increased likelihood of sperm banking completion. 110 Psychosocial providers can assist patients and families in the decision-making process about fertility preservation, particularly when AYA patients are distressed about the potential infertility associated with cancer treatment. 106 The Oncofertility Consortium, a group of clinicians and researchers in the United States, was formed in 2007 to address reproductive barriers facing AYA patients and to identify research priorities in this area.…”
Section: Fertility Preservationmentioning
confidence: 99%
“…It was indicated that, irrespective of whether adolescents (or parents) underreported, overreported, or accurately reported risk, they were equally likely to attempt sperm banking [Fisher exact test = 0.185/ χ 2 = 3.322, P = .190 (adolescents); Fisher exact test = 0.555/ χ 2 = 1.370, P = .504 (parents)]; note that although Fisher exact test accounts for small cell frequencies, the smallest cell included only n = 3). For more details regarding sperm banking outcomes, please see a previously published manuscript …”
Section: Resultsmentioning
confidence: 99%
“…All procedures followed the ethical standards of the US Federal Policy for the Protection of Human Subjects and were approved by the Institutional Review Boards at all sites (SJCRH#Pro00001628). Data presented here are part of a larger study about sperm cryopreservation among adolescent cancer patients …”
Section: Methodsmentioning
confidence: 99%
“…Up to 60% of male childhood cancer survivors experience fertility impairment, and while sperm banking is generally noninvasive, only ∼25% of eligible males bank sperm before treatment . Despite efforts to address common barriers to FP (for example, inadequate knowledge, urgency to begin treatment, and costs), rates remain low, suggesting that other factors likely affect FP decisions . Specifically, adolescents may struggle with anticipating future parenthood goals and making such decisions .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, adolescents may struggle with anticipating future parenthood goals and making such decisions . Further, masturbating to collect a semen sample may be challenging for those with little sexual experience and/or physical and psychological discomfort due to cancer …”
Section: Introductionmentioning
confidence: 99%